Quantum non-Gaussianity of light and atoms. (May 2022) - Lachman, Lukáš; Filip, Radim
Abstract: Quantum non-Gaussian states of photons and phonons are conclusive and direct witnesses of higher-than-quadratic nonlinearities in optical and mechanical processes. Moreover, they are proven resources for quantum sensing, communication and error correction with diverse continuous-variable systems. This review introduces theoretical analyses of nonclassical and quantum non-Gaussian states of photons and phonons. It recapitulates approaches used to derive operational criteria for photons tolerant to optical losses, their application in experiments and their nowadays extension to quantum non-Gaussian photon coincidences. It extends to a recent comparison of quantum non-Gaussianity, including robustness to thermal noise, and sensing capability for high-quality phononic Fock states of single trapped cooled ions. The review can stimulate further development in the criteria of quantum non-Gaussian states and experimental effort to prepare and detect such useful features, navigating the community to advanced quantum physics and technology. Highlights: Introduction to nonclassical states of photons and phonons. Theoretical approaches for quantum non-Gaussian photonic and phononic states with experimental applications. Operational criteria of nonclassicality and quantum non-Gaussianity for multiphoton and multiphonon states. Hierarchy of quantum non-Gaussianity for Fock states of photons and phonons with experimental tests.